Controllability Results for Nonlinear Higher Order Fractional Delay Dynamical Systems with Control Delay - Sivabalan, M.; Sivasamy, R.; Sathiyanathan, K. (Journal of Applied Nonlinear Dynamics, 2026)
This paper establishes a set of sufficient conditions for the nonlinear fractional delay dynamical systems with control delay of order 1 < α < 2, and the delays are in state variable as well as control variable. The solution representations are provided. The main tool are the Mittag-Leffler matrix function and the Schaefer’s fixed point theorem. Examples are presented to illustrate the results.